An Event Based Multiple Target Tracking - Vivek A (International Journal of Advanced Science and Technology, 2020)
This paper describes an algorithm for tracking multiple moving targets. The aim is to track multiple targets with the help of a Unmanned Aerial Vehicle (UAV). The distance of the targets from the UAV is monitored. Once there is change in velocity of target, an event is generated. The event based technique help to improve the efficiency of UAV. An algorithm is developed to track all the targets, within the specified area. A five target algorithm is developed in this stage. A simulation is also performed to validate the proposed algorithm.